Application of Literacy Journal as a means of increasing literacy in students - Halisa, Siti Nur; Rakhman, Patra Aghtiar; Rokmanah, Siti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to find out how the application of literacy journals as a means of increasing literacy in students at SD YPWKS V. This research method is descriptive qualitative research with a case study approach. Data collection techniques used in this study were interviews and observations. Data analysis is carried out with three lines of activities, namely data reduction, data presentation, and conclusion. The subjects in this study were teachers and students of grade V SD Blok YPWKS V. The results of this study showed that in the application of literacy journals using 3 stages, namely the habituation stage, the development stage, and the learning stage. The method used in the application of literacy journals is an assignment method that aims to foster independence in students to carry out literacy activities both at school and at home, so that students can increase interest and ability in literacy activities.